PENEGAKAN SYARIAT ISLAM DI INDONESIA (Perspektif Ekonomi) - Kholis, Nur (Al-Mawarid Jurnal Hukum Islam, 2006)
The article below traces to describe the development of Syariat Islam on economic enforcement in Indonesia. The description is covered Islamic banking, Islamic insurance, Islamic capital market, Syariah Obligation, Islamic unit trust/mutual fund, Islamic microfinance institution etc. The development of the Islamic economic institution in Indonesia show a rapid development. It support society optimism to develop more in the future. Morever the performance of Islamic banking practice at the end of the year 2006 show better performance than conventional banks, especially in the composition of money saving at SBI/SWBI, nonperforming financing or loan, and financing or loan to deposit ratio. It is hope that this evidence inspire all muslims in Indonesia to support and participate in developing Islamic economic enforcement in the future, especially in the area of zakat, wakaf, Islamic insurance, Islamic banking, sukuk or syariah obligation and Islamic microfinance. Kata Kunci: Syariat Islam, ekonomi Islam, penegakan Syariat Islam